Research advances and development trends of wire-based laser directed energy deposition additive manufacturing technology - YUAN Yucheng; SONG Jun; LUO Jiajie; LI Xiangru; SONG Bo; SHI Yusheng (Cailiao gongcheng)
With the development of fields such as aviation， aerospace， and navigation， the service conditions for high-end equipment have become increasingly stringent， placing higher demands on the manufacturing industry. Additive manufacturing technology， also known as 3D printing technology， has significant advantages over traditional manufacturing techniques in producing complex shapes and structures， and it is expected to achieve specific location printing and structural printing with unique properties in three-dimensional space. Wire-based laser directed energy deposition （W-LDED） technology， as an important branch of additive manufacturing， has notable advantages such as high efficiency， high precision， and high material utilization， making it promising for applications in the manufacturing of high-end equipment. Despite the many advantages of W-LDED technology， there are still numerous challenges regarding the selection of process parameters， multiple thermal cycles， and the precise control and repeatability of the manufacturing process. The deposition quality and manufacturing stability are influenced by various factors， and addressing these current challenges is a key focus of research both domestically and internationally. Based on this， this paper provides a detailed introduction to the current research status of W-LDED technology from three aspects： process parameter optimization， deposition quality analysis， and microstructural composition control. It analyzes the impact of different parameters on forming quality and manufacturing stability， proposes optimization strategies， summarizes the current application scenarios of W-LDED technology， and presents ideas for the future development trends of this technology，including material innovation and the development of multifuctional composites，research on forming mechanisms，establishing predictive models for process-defect-microstructure property relationships， new hybrid additive/subtractive manufacturing methods，and the development of large-scale，high-precision，and multifuctional equipment.